2016
DOI: 10.1186/s12891-016-1293-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative, retrospective study of peri-articular and intra-articular injection of tranexamic acid for the management of postoperative blood loss after total knee arthroplasty

Abstract: BackgroundIntra-articular injection of tranexamic acid (TXA) is known to be effective in controlling blood loss after total knee arthroplasty (TKA). However, this method has some disadvantages, such as TXA leakage due to soft tissue release. Peri-articular injection provides an alternative to intra-articular administration of TXA. This study aimed to evaluate the effects of peri-articular injection of TXA in reducing blood loss after TKA and compare them to those of intra-articular TXA injection.MethodsThis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…Not only can reduce blood loss, but also which can inhibit plasmin and lower in ammation. Therefore, in this study every patient administered intravenously TXA [16,8].…”
Section: Discussionmentioning
confidence: 99%
“…Not only can reduce blood loss, but also which can inhibit plasmin and lower in ammation. Therefore, in this study every patient administered intravenously TXA [16,8].…”
Section: Discussionmentioning
confidence: 99%
“…previously cement was placed between the bone-cutting site and implant component to reduce bone oozing, and IAI of TXA was employed to reduce blood oozing after synovectomy. However, muscle oozing was not effectively managed using this approach, and the studies on IMI of TXA in unilateral TKA are limited [13][14][15]. Mao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al. demonstrated that IMI and IAI of TXA e ciently at reducing blood loss during TKA compared with a control group; but the difference between IMI and IAI was nonsigni cant [13]. Pinsornsak et al reported that the antibleeding effects of intramuscular injected and intravenous injected TXA were similar [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with chronic kidney disease (CKD) have been reported to carry higher risks of cardiovascular disease, increased blood transfusion and postoperative infection, and acute kidney disease (AKD) after TKA [ 3 ]. The estimated blood loss after TKA ranges from 1000 to 1400 ml and results in a blood transfusion rate of 0–17.5% [ 4 7 ]. Anemia-related AKD via a hypotension episode or a decrease in oxygen-carrying capacity has been reported [ 8 ].…”
Section: Introductionmentioning
confidence: 99%